Association of Acne Tarda with Endocrinological Disorders - Evgenia Makrantonaki; Christos C. Zouboulis (MDPI AG, 2022)
Acne tarda is defined as acne that develops (late-onset acne) or continues (persistent acne) after 25 years of age. The disease is more common in women. The etiology of acne tarda is still controversial, and a variety of factors such as endocrinological disorders including hyperandrogenism and hyperandrogenemia, stress, modern western diet, ultraviolet irradiation, drugs and cosmetics have been implicated. In particular, women with acne tarda and other symptoms of hyperandrogenism such as hirsutism and androgenetic alopecia have a high probability of endocrine abnormalities such as polycystic ovarian syndrome, primary ovarian insufficiency, Cushing's syndrome and late-onset adrenogenital syndrome. Virilization is a relatively uncommon feature of hyperandrogenemia and its presence often suggests an androgen-producing tumor. Treatment is similar to that of acne in adolescence; however, long-term treatment over years or decades may be required. A thorough history, a focused clinical examination and an interdisciplinary approach together with gynecologists and endocrinologists are extremely helpful in diagnostic evaluation and therapy of patients with acne tarda.